Forms of Play and How they Influence Acquisition of Numeracy Skills among Preschool Children in Kenya - Muema, Mary M.; Koech, Peter Kibet; Muriungi, Pamela (HRMARS, 2018)
This study sought to underscore the influence of forms of play in the teaching of Mathematics, particularly acquisition of numeracy skills among children in preschool. The study was done among preschool children in Kenya. Its purpose was to assess the influence of forms of play on acquisition of numeracy skills in Early Childhood Development and Education (ECDE) centers. In this regard, while focusing on preschool institutions in Kenya the objective of the study was to find out forms of play and how they influence teaching of numeracy skills among preschool children in Kenya. The study utilized qualitative research design. The dependent variable for the study was the acquisition of numeracy skills among children in preschool institutions in Kenya, while independent variable is influence of form of play. The target population comprised of all preschool children and preschool teachers and head teachers in Kenya. The research instruments was piloted in two public and one private preschool institution that were not included in the study sample, but within the target population. The data collected was edited and coded according to themes that emanated from the research objective. Qualitative data was derived from open-ended responses received during interviews. The quantitative data was analyzed and presented using descriptive statistics such as frequency distribution, tables and percentages and also in narrative form. Qualitative data was presented in narrative form. Questionnaire, interview and observation schedules were used for data collection, while descriptive statistics was used in data analysis. The study established that (39%) of ECDE teachers were not decided whether different forms of play enhanced acquisition of numeracy skills in ECDE Kathiani sub county. Thus, the study recommended that ECDE teachers should be made to understand the importance of play in enhancing acquisition of numeracy skills in ECDE centers. ECDE teachers should undertake further proficiency training on planning, organizing and delivering of content in ECDE teaching and learning. It is expected that the findings of this study will contribute to the efforts towards early interventions to improve numeracy learning outcomes of among learners in Kenya. The study is of significant to the Ministry of Education, Kenya Institute of Curriculum Development, publishers and developers of early childhood education materials and teachers as well as owners and sponsors of ECDE institutions.
Keywords: Forms of Play; Preschool Children; Acquisition; Numeracy skills